3C-BASED METHODS FOR 3D GENOME ORGANIZATION ANALYSIS - N. R. Battulin; V. S. Fishman; Yu. L. Orlov; A. G. Menzorov; D. A. Afonnikov; O. L. Serov (Вавиловский журнал генетики и селекции, 2014)
The 3D organization of an eukaryotic genome plays an important role in nuclear gene expression. Until recently, studies of this organization were limited by light microscopy and electron microscopy methods. The development of chromosome conformation capture (3С) methods allowed studying genome-wide chromosomal contacts by using only molecular methods. Nowadays, numerous 3C-based methods have been developed to reconstruct the 3D organization of eukaryotic genomes.